Get reliable answers to your questions at Westonci.ca, where our knowledgeable community is always ready to help. Connect with a community of professionals ready to help you find accurate solutions to your questions quickly and efficiently. Discover detailed answers to your questions from a wide network of experts on our comprehensive Q&A platform.
Sagot :
Let's go through the process of solving for [tex]\(2x - 3y\)[/tex] step-by-step, given [tex]\(x = 3 + 8i\)[/tex] and [tex]\(y = 7 - i\)[/tex].
1. Multiply [tex]\(x\)[/tex] by 2:
[tex]\[ 2x = 2 \cdot (3 + 8i) = 6 + 16i \][/tex]
2. Multiply [tex]\(y\)[/tex] by 3:
[tex]\[ 3y = 3 \cdot (7 - i) = 21 - 3i \][/tex]
3. Subtract [tex]\(3y\)[/tex] from [tex]\(2x\)[/tex]:
[tex]\[ 2x - 3y = (6 + 16i) - (21 - 3i) \][/tex]
4. Distribute the subtraction:
[tex]\[ 2x - 3y = (6 - 21) + (16i + 3i) \][/tex]
5. Combine the real and imaginary parts:
[tex]\[ 2x - 3y = -15 + 19i \][/tex]
Therefore, the equivalent expression for [tex]\(2x - 3y\)[/tex] is [tex]\(-15 + 19i\)[/tex]. So,
[tex]\[ 2x - 3y \longrightarrow -15 + 19i \][/tex]
1. Multiply [tex]\(x\)[/tex] by 2:
[tex]\[ 2x = 2 \cdot (3 + 8i) = 6 + 16i \][/tex]
2. Multiply [tex]\(y\)[/tex] by 3:
[tex]\[ 3y = 3 \cdot (7 - i) = 21 - 3i \][/tex]
3. Subtract [tex]\(3y\)[/tex] from [tex]\(2x\)[/tex]:
[tex]\[ 2x - 3y = (6 + 16i) - (21 - 3i) \][/tex]
4. Distribute the subtraction:
[tex]\[ 2x - 3y = (6 - 21) + (16i + 3i) \][/tex]
5. Combine the real and imaginary parts:
[tex]\[ 2x - 3y = -15 + 19i \][/tex]
Therefore, the equivalent expression for [tex]\(2x - 3y\)[/tex] is [tex]\(-15 + 19i\)[/tex]. So,
[tex]\[ 2x - 3y \longrightarrow -15 + 19i \][/tex]
Thanks for stopping by. We are committed to providing the best answers for all your questions. See you again soon. Thank you for your visit. We're dedicated to helping you find the information you need, whenever you need it. Your questions are important to us at Westonci.ca. Visit again for expert answers and reliable information.